Designing Problem-Based Learning With a Flipped Classroom Design in Appreciating Fiction Prose - Jasril Jasril; Dadang Sunendar; Sumiyadi Sumiyadi; Yeti Mulyati (AL-ISHLAH: Jurnal Pendidikan, 2024)
The appreciation of fictional prose can be used to shape the ethics and morals of students. Various approaches and learning models have been developed to help sharpen students' skills in appreciating fictional prose, although satisfactory results have not been achieved overall. Therefore, the aim of this research is to design a learning concept that has the potential to enhance students' capabilities in understanding and appreciating fictional prose. The research data is sourced from 12 articles obtained through Google Scholar, Sage Journals, Taylor and Francis, ProQuest, and Scopus databases. The articles used as data sources are related to the appreciation of fiction prose, flipped classrooms, and problem-based learning. Data collection and analysis were conducted using the read-note-analyze technique. The research findings affirm that a problem-based learning approach, combined with the implementation of a flipped classroom design, holds significant potential for improving students' appreciation skills of fictional prose and can be efficiently applied in the learning process. Furthermore, this model accommodates the use of technology in learning and facilitates group work among students.